Records Rock Art (Engravings) in the Santa Catarina Coast: a literature review on studies in this region - Filho, S. L. L.; Martinelli, S. A.; Kestering, C. (Scientia Plena, 2012)
The graphic records shown in different regions of Brazil have long been associated with companies from outside of Brazil. The associations linked forms of written features as belonging to the Phoenicians, Egyptians and Mesopotamians. However, since the decade of 50/60 these approaches have been put aside to make way for a systematic study which looked at the records as a means of graphic communication associated with the different groups who settled and interacted in all the land Brasillis. With regard to the study of graphic records (prints) of the coastal region of Santa Catarina and neighboring islands can be seen through a literature review that there is a incogluence about the authorship and dating for these events. So, this article raises some propositions about the types of prints made in the region and propose studies conducted through the three possible authorship for these social manifestations pictographic.